Path to Personalized Medicine for Type 2 Diabetes Mellitus: Reality and Hope - Hamid Reza Aghaei Meybodi; Mandana Hasanzad; Bagher Larijani (Acta Medica Iranica, 2017)
Type 2 diabetes mellitus (T2DM) is recognized as a public health problem and increasingly prevalent illness. Key elements of the guideline for diabetes care are based on evidence-based medicine approach and apply for population, not individuals. However, individualized care can improve diabetes management. Personalized medicine is otherwise called precision medicine tries to find better prediction, prevention, and intervention for T2DM individuals. Precision medicine in diabetes refers to the utility of genomics data of a patient with diabetes to provide the most effective diagnosis strategies and treatment plans. Over 100 genetic loci influence susceptibility to T2DM. Genomics data together with the potential of other “Omics” and clinical evidence-based data will lead to diabetes care improvement in the context of personalized medicine in the near future. Breakthrough of technologies enables much greater improvements in the understanding of individual variations that may alter the T2DM outcome. This article represents a comprehensive review of current knowledge on the impact of personalized medicine in T2DM.